Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Konsumen - Gozali, Ahmad (JUBISMA, 2024)
ABSTRAK Businesses that use the marketing concept must pay attention to consumer behavior and the factors that influence their decisions because this concept is one way to achieve company goals, namely to find out the needs and desires of consumers or target markets and how to provide satisfaction that consumers or buyers expect effectively and efficiently. The purpose of this study is to identify what variables influence consumer decisions to buy a product. Based on the formulation of the article, the results, and the discussion reviewed and discussed in this article, it can be concluded that many factors influence consumer decisions to buy a product, including product price, product quality, quality of service, promotion, location, consumer confidence and store atmosphere. Keywords: Purchasing Decisions, Consumers.